2004
DOI: 10.2343/geochemj.38.345
|View full text |Cite
|
Sign up to set email alerts
|

Protolith age and exhumation history of metagranites from the Dabie UHP metamorphic belt in east-central China: A multi-chronological study

Abstract: Metagranites (granitic orthogneisses) constitute one of the important lithologic units in the Dabie ultrahigh pressure metamorphic belt. They often display direct contact with paragneisses and eclogites. TIMS zircon U-Pb dating on the metagranites reveal that their protolith was crystallized as granitoids in Neoproterozoic ages of 755 to 611 Ma and thus correspond to rift magmatism associated with breakup of the Rodinia supercontinent in the northern margin of the Yangtze Block. Zircon U-Pb age and Ar-Ar ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 70 publications
(103 reference statements)
0
2
0
2
Order By: Relevance
“…For example, Rowley et al [3] reported an upper intercept age of 805 ± 15 Ma for gneissic metagranites at Shima, and Chavagnac et al [14] gave an upper intercept age of 720 ± 26 Ma for those at Bixiling, and considered them to be the protolith ages. Wang et al [15] reported several sets of upper and lower intercept ages for different metagranite plutons, such as 726 ± 15 Ma and 224.5 ± 6.3 Ma for Shuanghe, 714 ± 14 Ma and 209 ± 14 Ma for Bixiling, 720 ± 61 Ma and 197 ± 21 Ma for Xindian, and 755 ± 34 Ma and 299 ± 33 Ma for Huangzhen, and considered the upper and lower intercept ages to be the protolith ages and the subsequent UHP and/or retrograde metamorphic ages, respectively. The above dating results suggest that the protoliths of the gneissic metagranites in Dabie region were mainly formed in Neoproterozoic (700-800 Ma) [16].…”
Section: Geochronologymentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Rowley et al [3] reported an upper intercept age of 805 ± 15 Ma for gneissic metagranites at Shima, and Chavagnac et al [14] gave an upper intercept age of 720 ± 26 Ma for those at Bixiling, and considered them to be the protolith ages. Wang et al [15] reported several sets of upper and lower intercept ages for different metagranite plutons, such as 726 ± 15 Ma and 224.5 ± 6.3 Ma for Shuanghe, 714 ± 14 Ma and 209 ± 14 Ma for Bixiling, 720 ± 61 Ma and 197 ± 21 Ma for Xindian, and 755 ± 34 Ma and 299 ± 33 Ma for Huangzhen, and considered the upper and lower intercept ages to be the protolith ages and the subsequent UHP and/or retrograde metamorphic ages, respectively. The above dating results suggest that the protoliths of the gneissic metagranites in Dabie region were mainly formed in Neoproterozoic (700-800 Ma) [16].…”
Section: Geochronologymentioning
confidence: 98%
“…The quartz grains are anhedral and display apparent wavy extinction, and some of them occur as lenticular poly-crystal aggregations. Plagioclases in Huangzhen, Daba, Shima and Shuanghe gneissic metagranites are mainly albite (An = 1-10), whereas those in Sanzusi pluton are albite-oligoclase (An = [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. They are all euhedral to subhedral, and lath in shape, with some grains showing inhomogeneous extinction due to metamorphism.…”
Section: General Geology and Petrologymentioning
confidence: 99%
“…对区内片麻状变质花岗岩的年龄前人主要运用 ID-TIMS 方法测定, 如 Rowley 等 [3] 测得石马片麻状 变质花岗岩的上交点年龄为(805±15) Ma, Chavagnac 等 [14] 测得碧溪岭片麻状变质花岗岩的上交点年龄为 (720±26) Ma, 并认为它们应代表原岩的形成年龄. Wang 等 [15] [16] , 但 由于 ID-TIMS 方法无法进行原位微区分析, 对于具 有复杂历史的锆石样品会得出混合年龄, 从而导致 无意义的定年结果.…”
Section: 年代学unclassified
“…他认为 A 型花岗岩 可进一步区分为构造环境及来源不同的 A 1 和 A 2 两组, A 1 组以其 Y/Nb 和 Y/Ta 比值与洋岛玄武岩相似为特 征, 岩浆起源于地幔并产于大陆裂谷或地幔热柱、热 点环境; A 2 组其比值则可由类似平均地壳变化至类 似岛弧玄武岩, 岩浆起源于地壳或由岛弧岩浆作用 派生, 产于后碰撞或后造山的张性构造环境. 在 Eby 提出的 A 型花岗岩亚类判别图解上, 原岩具有 A 型 [15] 花岗岩特性的第一组片麻状花岗岩均投影在 A 2 区(图 9, 10), 显示与岛弧玄武岩(IAB)的地球化学特征具亲 缘性. 结合在相对原始地幔标准化的蛛网图上, Sr, P, Ti, Nb 和 Ta 等元素呈显著的亏损特征, 表明这些片 麻状变质花岗岩的源区可能与俯冲作用有密切的联 系, 其原岩应形成于后碰撞或后造山的伸展引张环 境.…”
Section: 讨论unclassified